ANALISIS FAKTOR YANG MEMENGARUHI KEPATUHAN MINUM OBAT PASIEN HIPERTENSI DI PUSKESMAS TELUK NIBUNG KOTA TANJUNG BALAI - Nurhayati, Nurhayati; Rifai, Achmad; Yosepha Ginting, Desideria (NHM PRESS, 2023)
Hypertension is a condition where the systolic blood pressure is > 140 mmHg while the diastolic blood pressure is > 90 mmHg on repeated examinations. Nonadherence in taking medication regularly can increase the risk of complications from high blood pressure. The aim of the study was to analyze the factors that influence medication adherence in hypertensive patients at the Teluk Nibung Health Center, Tanjung Balai City, in 2023. This study was an analytic observational study with a cross-sectional study design. The population is all hypertensive patients who carry out outpatient examinations at the Teluk Nibung Health Center, Tanjung Balai City from September 2022 to November 2022, a total of 281 people. The sample used the slovin formula as many as 74 people. The result of this study showed that the influence of age (p=0.000), gender (p=0.000), education (p=0.001), employment (p=0.001), length of suffering (p=0.004), participation in health insurance (p=0.000) , access to health services (p=0.001), knowledge (p=0.000), and family support (p=0.000), from health worker support (p= 0.007) on adherence to taking medication for hypertension patients at the Teluk Nibung Health Center, Tanjung Balai City in 2023. The multivariate result of the variable that most influences adherence to taking medication for hypertensive patients is health insurance participation because it has the largest regression coefficient (B) value of 31.535. It is recommended for people with hypertension to regularly participate in prolanis activities every month, in addition to medical examinations, education for prolanis participants, SMS gateway reminders, home visits and club activities (gymnastics). With these activities can increase patient knowledge about the disease